STOCK STATUS, BIOLOGICAL REFERENCE POINT AND MANAGEMENT IMPLICATIONS OF PAINTED SPINY LOBSTER (Panulirus versicolor Latreille, 1804) IN WEST PAPUA WATERS - Tirtadanu Tirtadanu; Helman Nur Yusuf; Chang Ik Zhang (Indonesian Fisheries Research Journal, 2022)
As the main target species with high economic value, painted spiny lobster (P. Versicolor) is highly vulnerable to fishing impacts. The study on stock status and biological reference points is needed to develop management strategies for sustainable lobster fisheries in West Papua. This research aimed to understand the stock status, obtain the natural reference points, and set the management tools for P. Versicolor fisheries in West Papua. The length-based assessment of P. Versicolor stock has been conducted to obtain the life history parameters and analyze the yield per recruit and spawning potential ratio. The growth of overfishing has occurred based on the current length at the selectivity of P. Versicolor, which is lower than the optimal selectivity. The indication of recruitment overfishing has been found based on the recent fishing mortality, which exceeds 24% of reference point F40%. A reduction of 24% from current fishing mortality and the minimum legal size of 83 mm is needed to obtain the optimal yield in sustainable conditions.